Multimerization interactions between protein-inspired single-chain random heteropolymers - Shayna L. Hilburg; Tianyi Jin; Priya Ganesh; Alfredo Alexander-Katz (PLoS ONE, 2026)
Single-chain nanoparticles (SCNPs) are attractive for their ability to interact with or behave akin to native proteins. In this work, we use molecular dynamics simulations to examine how SCNPs which are assembled non-covalently due to the hydrophobic effect and monomers with negative Flory-Huggins interaction parameters ( χ ) in water can interact with other macromolecules. The occurrence of multimerization is characterized for a methacrylate-based random heteropolymer system with heterogeneous surfaces and sequence behaviors. The system shows two primary interaction modes: (1) adsorbing through side-chain interactions similar to protein oligomerization and (2) maintaining their single-chain structures or with only transient interactions. For cases in which adsorption does occur, the small, amphiphilic methyl methacrylate monomers are shown to enrich at the points of contact. Hydrophobic residues are typically present at the interface when adsorption is prolonged, while hydrophilic monomers associate in more transient inter-polymeric interactions. Finally, we demonstrate that polymer conformation of a single polymer sequence plays a large role in multimerization, while the variation among these conformations is statistically indistinguishable from the variation amongst different sequences.